Eosinophilic pneumonias in children: A review of the epidemiology, diagnosis, and treatment. Issue 2 (30th December 2015) - Giovannini‐Chami, Lisa; Blanc, Sibylle; Hadchouel, Alice; Baruchel, André; Boukari, Rachida; Dubus, Jean‐Christophe; Fayon, Michael; Le Bourgeois, Muriel; Nathan, Nadia; Albertini, Marc; Clément, Annick; de Blic, Jacques
Summary: Pediatric eosinophilic pneumonias (EPs) are characterized by a significant infiltration of the alveolar spaces and lung interstitium by eosinophils, with conservation of the lung structure. In developed countries, EPs constitute exceptional entities in pediatric care. Clinical symptoms may be transient (Löffler syndrome), acute (<1 month and mostly <7 days), or chronic (>1 month). Diagnosis relies on demonstration of alveolar eosinophilia on bronchoalveolar lavage, whether or not associated with blood eosinophilia. EPs are a heterogeneous group of disorders divided into: (i) secondary forms (seen mainly in parasitic infections, allergic bronchopulmonary aspergillosis, and drug reactions); and (ii) primary forms (eosinophilic granulomatosis with polyangiitis, hypereosinophilic syndrome, idiopathic chronic eosinophilic pneumonia, and idiopathic acute eosinophilic pneumonia). Despite their rarity, the etiological approach to EP must be well‐defined as some causes can be rapidly life‐threatening without initiation of the proper treatment. This approach (i) eliminates secondary forms, with comprehensive history taking and minimal biological assessment, (ii) is oriented in primary forms by the acute or chronic setting, and the existence of extrapulmonary symptoms. Treatment of primary forms has traditionally relied on corticosteroids, usually with a dramatic response. Specific treatments or the adjunction of corticosteroid‐sparing treatment or immunosuppressors are currently being evaluated in order to improve the prognosis and the side effects associated with corticosteroid treatment in a pediatric setting.Pediatr Pulmonol. 2016;51:203–216. © 2015 Wiley Periodicals, Inc.